The Influence of Personal Factors and Perceived Work Experiences on Employee Turnover and Absenteeism - Spencer, Daniel G.; Steers, Richard M. (Academy of Management Journal, 1980)
The article presents a study which examined the relative influence of personal factors and work experiences of employees on employee turnover and absenteeism. According to the results of the study, labor turnover and absenteeism are independent of work experiences and personal factors. The study also determined that absenteeism is predicted more accurately by personal factors than by work experiences. The author notes that personal characteristics exhibit a higher correlations with absenteeism than with turnover.